2021
DOI: 10.1111/cge.13960
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic RFC1 pentanucleotide repeat expansions in Greek patients with late‐onset ataxia

Abstract: Cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) has been recently linked to biallelic expansions of a pentanucleotide repeat in the replication factor C subunit 1 (RFC1) gene. Herein, we sought to investigate the presence of pathological RFC1 expansions in selected Greek patients with late‐onset ataxia and delineate the phenotypic spectrum of genetically confirmed CANVAS in the Greek population. We screened genetically a total of 77 selected index patients, 67 originating from a cerebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…It is notable that our diagnostic yield of RFC1 repeat expansions was lower than that in other ataxia cohorts (1.8 vs. 3.2-22%) (1,(18)(19)(20). This may be accounted for by the inclusion of cases with MSA in our case series, and the predominant sporadic cases (80%) without family history and consanguinity.…”
Section: Discussionmentioning
confidence: 59%
“…It is notable that our diagnostic yield of RFC1 repeat expansions was lower than that in other ataxia cohorts (1.8 vs. 3.2-22%) (1,(18)(19)(20). This may be accounted for by the inclusion of cases with MSA in our case series, and the predominant sporadic cases (80%) without family history and consanguinity.…”
Section: Discussionmentioning
confidence: 59%
“…The true prevalence of this phenotype in RFC1 -related disease is currently difficult to gauge because the recent retrospective studies, by their very nature, lack consistent data on formal vestibular function testing and may be under-recognizing the presence of peripheral vestibular hypofunction. 4 , 13 , 16 Of interest Gisatulin et al 8 reported this phenotypic combination in one of the only studies to date where all participants have received objective vestibular assessment.…”
Section: Major Phenotypic Characteristics Of Rfc1 ...mentioning
confidence: 99%
“…Unfortunately, several studies have neglected to perform the relevant investigations and have instead relied on bedside assessments or incompletely described methodology. 4,[10][11][12][13]16 Key examples of this are the clinical vs video head impulse test (HIT) and the bedside vs electrophysiologic assessment of somatosensory function. 40,41 The exception here may be an absence of cerebellar atrophy on MRI in the early stage of cerebellar disease where bedside examination findings may be more sensitive than MRI findings.…”
Section: Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, two European groups demonstrated that bi-allelic [(AAGGG)exp/(AAGGG)exp] of RFC1 account for 30–34% of their patients with pure sensory ataxic neuropathy or idiopathic axonal polyneuropathy ( 8 , 24 ). Our findings further supported their observation, albeit not as high as their prevalence, and validated its commonness not only in European studies but also in Asian studies.…”
Section: Discussionmentioning
confidence: 99%